Reterritorialization In a Fandom of Popular Korean Culture: Identity Reproduction To a Korean Wave - Ismadiah Wulandari (JSSH (Jurnal Sains Sosial dan Humaniora), 2020)
Information technology and the role of the media encourage the emergence of cultures that are loved by many people around the world. Culture becomes a popular culture because of the contribution of mass media or new media. Korean culture is one of popular culture in Indonesia today. Various behaviors of Indonesian people mimic the culture in Korea, from the style of dress, lifestyle, hairstyle to even the style of speech sometimes imitating the cultural habits.In a world that has deteritorialized, new meanings shown locally because the existence of territorial not stay in one location. Deterritorialization contain reterritorialization with the relocation of meaning in different spaces and places than before.  Through literature review and observation, the research aims to understanding formation identity process of Korean fandom (Korean wave) and its relevance to the reterritorialization’s context of Korean fandom (Korean wave) in Lampung.  The relocation of ke-Korea-an combined with territoriality requirement as part of the adaptation to location. This results in a number of locality such as the creation of local environment in Lampung.  A scheme that can be displayed from this case is the negotiation of identity through the re-territorialization, cultural borrowing, fictive kinship as results of social boundaries from community with the production locality.